Dynamic capacity and variable runway configurations in airport slot allocation - Cheung, Wai Lun (2021)
The airport slot allocation procedure relies on a (fixed) capacity to allocate slots to airlines, which often leads to under/over utilization of slots, depending on how conservative the airport planners are. This demand and capacity imbalance over the peak period can best be addressed during the strategic planning phase by displacing flights from their originally allocated slots to neighboring ones with available capacity. The proposed Mixed Integer Programming (MIP) model addresses peak airport traffic with a leveling effect through minor adjustment of the demand with respect to a dynamic capacity derived from an analytical capacity model. The analytical capacity model provides a dynamic capacity estimation over the planning horizon based on a varying flight mix. Our approach also allows for exploration of possible runway configurations, arrival/departure priority, and operational modes (segregated/ mixed) to ensure that the higher levels of demand during the strategic planning phase does not lead to excessive delays on the day of operations. The MIP model lexicographically optimizes the flight slots, minimizing the number of displaced flights and total slot displacement for all flights, subject to scheduling, maximum acceptable slot displacement, capacity, and runway configuration constraints.